Nuclear Factor-κB Activation Contributes to Vascular Endothelial Dysfunction via Oxidative Stress in Overweight/Obese Middle-Aged and Older Humans - Pierce, Gary L.; Lesniewski, Lisa A.; Lawson, Brooke R.; Beske, Stacy D.; Seals, Douglas R. (Circulation (New York, N.Y.), 2009)
Background— We tested the hypothesis that nuclear factor-κB (NF-κB) activity contributes to vascular endothelial dysfunction with aging and obesity in humans. Methods and Results— We conducted a randomized, double-blind, placebo-controlled crossover study in 14 nondiabetic overweight or obese (body mass index ≥25 kg/m 2 ) middle-aged and older (age 52 to 68 years) adults. Salsalate (nonacetylated salicylate, 4500 mg/d), a compound that inhibits NF-κB activity, or placebo was administered for 4-day periods. Plasma salicylate concentrations reached the midtherapeutic range (21.8±1.1 mg/100 mL, P ≤0.0001 versus placebo) by day 4 of salsalate treatment. Salsalate increased expression of the inhibitor of NF-κB and reduced total and nuclear expression of NF-κB in endothelial cells obtained from the subjects (all P <0.05). Salsalate increased brachial artery flow-mediated dilation by 74% (from 4.0±0.4% to 6.6±0.5%, P <0.001) but did not affect endothelium-independent dilation ( P =0.83). The change in brachial artery flow-mediated dilation with salsalate was inversely related to baseline flow-mediated dilation ( r =−0.77, P <0.01). Infusion of vitamin C increased brachial artery flow-mediated dilation during placebo ( P <0.001) but not after salsalate ( P =0.23). Salsalate reduced nitrotyrosine ( P =0.06) and expression of NADPH oxidase p47 phox ( P <0.05) in endothelial cells obtained from the subjects but did not influence circulating or endothelial cell inflammatory proteins. Conclusions— Our findings provide the first direct evidence that NF-κB, in part via stimulation of oxidative stress, plays an important role in mediating vascular endothelial dysfunction in overweight and obese middle-aged and older humans.